Possible breeding record for the Grey-headed Bush-shrike Malaconotus blanchoti in Boskruin, Randburg (Pentads 2600_2755 and 2605_2755) - Branfield, Andy; Clough, Anthony (Biodiversity Observations, 2014)
The Grey-headed Bush-shrike Malaconotus blanchoti is a large and colourful species of bush-shrike. However, it is stealthy in habits and it is easy to overlook when it is not calling...